(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Studying the health characteristics of children with frequent and long-term morbidity, searching for new ways to reduce it are important tasks of the general health strategy for achieving the goal of "Health for All by the Year 2000" developed by the World Health Organization (WHO). Solving the problem of frequently ill children will help strengthen the health of the younger generation. Reducing the number of frequently ill children will lead to a decrease in the morbidity of the entire child population. Rehabilitation of frequently ill children will improve the functional state of the body, general and local immunological reactivity, reduce the risk of developing chronic pathology, improve the physical and neuropsychic development of preschool children and the academic performance of schoolchildren, and prevent the emergence of unfavorable psychological characteristics.